Participant investment behavior and investment performance in defined contribution plans: Evidence from small firms in South Korea - Kyonghee Lee; Heejin Park (Global Business & Finance Review (GBFR), 2021)
Purpose: We investigate participant behaviors and the investment performance of defined contribution (DC) plans. Design/methodology/approach: Using unique data of 420,839 participants in 47,442 workplace pension schemes for small firms in South Korea, we examine participant investment behavior and the investment performance of DC plans. Findings: We find that participants exhibit extreme risk avoidance in their pension management, leading to lower investment returns. Additionally, most participants choose few investment products and initiate no trades. Finally, the pension service provider's DC investment menu affects participants' investment performance. Research limitations/implications: Given that our sample only covers the DC plans of firms with less than 30 employees, our findings may not be generalized to larger firms. However, the findings of this paper suggest that corporate pension schemes require careful design to account for participants' behavioral biases and their impact on retirement security, as well as the importance of plan design. Originality/value: This study contributes to corporate pension research by documenting the unique features of Korean DC plans in small-scale firms. Further this research presents the need for a pension policy for sustainable retirement income by showing the irrational investment behavior of employees in small-scale firms.
Keywords: 650; Defined Contribution Plan; Participant Investment Behaviors; Personal Rate of Return